Analisis Penjadwalan Proyek Pembangunan dengan Menggunakan Metode CPM Dan PERT - Rosita, Delia; candra candra, adi; Khairunnisa (Universitas Pamulang, 2024)
Rama Engineering is one of the companies that is moving in the field of construction that is currently working on the construction project of the University of Pamulang campus 3 Witana Harja. In the implementation of such construction projects there is usually a deadline every week, but the actual delay from the planning of 9 months to 11 months requires the calculation of the project scheduling. Project scheduling is one of the planning elements that can provide information about the schedule of plans and the progress of ongoing projects. To find out the optimal time of the project is done analysis using the CPM method and for the most possible duration in the acceleration of the building construction project is analyzed using the PERT method. The results of the analysis using the CPM method showed a 3-week acceleration where the initial project duration of 35 weeks was 32 weeks with a 3% accelerated presentation score with a critical path A – B – C – D – E – R – S – U, whereas the analysis with the PERT method saw a 1-week 6-day accelerations where the project initial duration for 35 weeks became 33.17 weeks with an accelerating presentation score of 1.87% with a Critical Path A - B - C - D - E - R - S - U. In conclusion, in order to minimize the completion time of the project as a whole, a combination of similar activities is carried out. . Keywords: CPM, Project Management, PERT